Supporting student agency with transmedia. Issue 1 (1st February 2019) - Hovious, Amanda; Shinas, Valerie Harlow; Harper, Ian
ABSTRACT: Student agency is defined as a student's sense of self‐control over his or her educational experiences. It is a critical aspect of learning among adolescents. One way to promote student agency in the classroom is through the integration of texts and tools that allow students to become producers and consumers of content. Transmedia—the creation and sharing of narrative across media—is such a tool. This poster presentation illustrates how transmedia can be used to support student agency and engagement, drawing on a foundational case study of middle‐grade students who interacted with the project, Inanimate Alice, an interactive novel that follows the adventures of Alice, a globetrotting girl who wants to be a game designer when she grows up. Future directions of the project are demonstrated via a new iteration of Inanimate Alice, a virtual reality (VR) gap story called Perpetual Nomads . The audience may experience Perpetual Nomads with a VR headset and learn about its implications for fostering student agency based on beta testing of the story with middle‐grade students. The presenters also discuss an upcoming research initiative that will further test the impact of Perpetual Nomads on digital and technological literacies—an important avenue for fostering student agency.